2020
DOI: 10.1155/2020/1057846
|View full text |Cite
|
Sign up to set email alerts
|

Failure Modes and Survival of Anterior Crowns Supported by Narrow Implant Systems

Abstract: The reduced hardware design of narrow implants increases the risk of fracture not only of the implant itself but also of the prosthetic constituents. Hence, the current study is aimed at estimating the probability of survival of anterior crowns supported by different narrow implant systems. Three different narrow implant systems of internal conical connections were evaluated (Ø3.5×10 mm): (i) Active (Nobel Biocare), (ii) Epikut (S.I.N. Implant System), and (iii) BLX (Straumann). Abutments were torqued to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This study's findings are in line with the existing literature on the failure modes of implant abutments. For instance, a study on the failure modes and survival of anterior crowns supported by narrow implant systems reported that the failure mode predominantly involved abutment and/or abutment screw fracture, highlighting the relevance of understanding specific failure patterns for different implant components [26]. Additionally, research on the effect of fatigue loading and the failure mode of different ceramic implant abutments provides insights into the failure modes of specific abutment materials, which is relevant to the observed distinctive failure patterns in the present study [27].…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings are in line with the existing literature on the failure modes of implant abutments. For instance, a study on the failure modes and survival of anterior crowns supported by narrow implant systems reported that the failure mode predominantly involved abutment and/or abutment screw fracture, highlighting the relevance of understanding specific failure patterns for different implant components [26]. Additionally, research on the effect of fatigue loading and the failure mode of different ceramic implant abutments provides insights into the failure modes of specific abutment materials, which is relevant to the observed distinctive failure patterns in the present study [27].…”
Section: Discussionmentioning
confidence: 99%
“…Three stress profiles for step stress accelerated-life testing (SSALT), based on the fatigue behavior of narrow implant systems previously published by our group [ 34 ], were used in the present study. Eighteen specimens per experimental group were distributed in a 3:2:1 ratio to mild (n = 9), moderate (n = 6) and aggressive (n = 3) stress profiles, named based on its step-wise load increase, as detailed elsewhere [ 24 , 29 , 31 , 33 ].…”
Section: Methodsmentioning
confidence: 99%